Hadith #2364 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Sami Maula Abi Bakr bin 'Abdur Rahman سمي مولى أبي بكر بن عبد الرحمن بن الحارث (Sunan Abi Dawud)
I have seen the Messenger of Allah (ﷺ) using a tooth-stick while he was fasting. Musaddad added in his version: “more often than I could count.”
Grade: Da'if

Hadith #2387 - Sunan Abi Dawud - Abd Rabba bin Sa'id bin Qays bin 'Amr عبد ربه بن سعيد بن قيس; Abdullah bin Muhammad bin Ishaq عبد الله بن محمد بن إسحاق; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Aisha bint Abi Bakr; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
A man asked the Prophet (ﷺ) whether one who was fasting could embrace (his wife) and he gave him permission; but when another man came to him, and asked him, he forbade him. The one to whom he gave permission was an old man and the one whom he forbade was a youth.
Grade: Sahih

Hadith #3427 - Sunan Abi Dawud - Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Abu Mas'ud al-Badri; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade earnings of a slave-girl unless it is known from where it came.
Grade: Hasan

Hadith #3480 - Sunan Abi Dawud - Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Abu Mas'ud al-Badri; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
The Prophet (ﷺ) forbade payment for cat.
Grade: Sahih

Hadith #3518 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Abu Bakr bin Muhammad bin 'Amr bin Hazm أبو بكر بن محمد بن عمرو بن حزم; Abu Hurairah; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Umar bin ‘Abdul-‘Aziz عمر بن عبد العزيز; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: The neighbour is most entitled to the right of pre-emption, and he should wait for its exercise even if he is absent, when the two properties have one road.
Grade: Sahih

Hadith #3519 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone becomes insolvent and the man (i.e. creditor) finds his very property with him, he is more entitled to it than anyone else.
Grade: Sahih

Hadith #3520 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The Prophet (ﷺ) said: If a man sells (his) property and the man who buys it becomes insolvent, and the seller does not receive the price of the property he had sold, but finds his very property with him (i.e. the buyer), he is more entitled to it (than others). If the buyer dies, then the owner of the property is equal to the creditors.
Grade: Sahih

Hadith #3521 - Sunan Abi Dawud - Abdullah bin 'Abdur Jabbar عبد الله بن عبد الجبار الخبائري زبريق; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي (Sunan Abi Dawud)
“If he paid something from the price (of the property), then he will be equal to the creditors in it.”
Grade: Sahih

Hadith #5008 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abdur Rahman bin al-Aswad; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Marwan bin al-Hakam bin Abi al-'As; Ubayy ibn Ka'b; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
It would have been better for him. I heard the Messenger of Allah (ﷺ) say: I think (or, I have been commanded) that I should be brief in what I say, for brevity is better.
Grade: Hasan